Comparison of antibiotic activities by using serum bactericidal activity over time. - Guglielmo, B J (1988)
In evaluating antimicrobial agents with similar spectra of activity, it is difficult to determine equivalent dosage regimens. In vitro potency, pharmacokinetic disposition, and other factors determine the usual dosing regimen. Knowledge of the serum bactericidal activity over time may assist in defining the potency of comparative antimicrobial agents. Cefoxitin and ceftizoxime, cephalosporins with gram-negative aerobic and anaerobic activity, have been promoted as monotherapy in the treatment of intra-abdominal infection. In a randomized, crossover study, six healthy volunteers received single 30-mg/kg doses of cefoxitin and ceftizoxime. Greater serum activity against Escherichia coli and Bacteroides fragilis was observed with ceftizoxime than with cefoxitin. The results suggest that ceftizoxime can be administered in a lower daily dosage than cefoxitin. We propose that the present study may serve as a prototype for future studies attempting to assess equivalent dosing regimens for antibiotics with similar spectra of activity.